2018
DOI: 10.1155/2018/4707389
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Biliary Stricture Development after Liver Transplantation in the Setting of Retained Prophylactic Intraductal Pediatric Feeding Tube: Case and Review

Abstract: The biliary anastomosis remains a common site of postoperative complications in liver transplantation (LT). Biliary complications have indeed been termed the “Achilles' heel” of LT, and while their prevention, diagnosis, and treatment have continued to evolve over the last two decades, various challenges and uncertainties persist. Here we present the case of a 33-year-old man who, 10 years after undergoing LT for idiopathic recurrent intrahepatic cholestasis, was noted to have developed pruritus and abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Non-anastomotic strictures account for approximately 10%-25% of post-LT BSs[ 18 ]. BSs are mainly linked to surgical skills, patients with small-sized ducts, donor-recipient bile duct size mismatch, longer operative time, total ischemia time, local ischemia, chronic rejection, older donor age, donor and recipient gender matching and initial disease recurrence like primary sclerosing cholangitis (PSC)[ 2 , 3 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-anastomotic strictures account for approximately 10%-25% of post-LT BSs[ 18 ]. BSs are mainly linked to surgical skills, patients with small-sized ducts, donor-recipient bile duct size mismatch, longer operative time, total ischemia time, local ischemia, chronic rejection, older donor age, donor and recipient gender matching and initial disease recurrence like primary sclerosing cholangitis (PSC)[ 2 , 3 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is predisposed to BL at the entry site and thus has become less commonly used[ 14 ]. Also, temporary internal biliary stents may be applied to cross the anastomosis site[ 19 ]; however, it has been reported that the incidence of BCs may increase with this technique[ 23 ].…”
Section: Introductionmentioning
confidence: 99%